Rapid detection of equine infectious anaemia virus nucleic acid by insulated isothermal RT‐PCR assay to aid diagnosis under field conditions. (13th November 2018) - Cook, R. F.; Barrandeguy, M.; Lee, P.‐Y. A.; Tsai, C.‐F.; Shen, Y.‐H.; Tsai, Y.‐L.; Chang, H.‐F. G.; Wang, H.‐T. T.; Balasuriya, U. B. R.
Summary: Background: Control of equine infectious anaemia (EIA) currently depends on serological diagnosis of infected equids. However, recently infected equids may not produce detectable anti‐EIAV antibodies up to 157 days post infection and so present a high transmission risk. Therefore, direct nucleic acid detection methods are urgently needed to improve EIAV surveillance and management programs in counties where the disease is endemic. Objectives: To evaluate a field‐deployable, reverse transcription‐insulated isothermal PCR (RT‐iiPCR) assay targeting the conserved 5′ untranslated region (5′ UTR)/exon 1 of the tat gene of EIAV. Study design: The analytical and clinical performance of the newly developed EIAV RT‐iiPCR was evaluated by comparison with a EIAV real‐time RT‐PCR (RT‐qPCR) along with the AGID test. Methods: Analytical sensitivity was determined using in vitro transcribed RNA containing the target area of the 5′ UTR/ tat gene and samples from two EIAV‐positive horses. Specificity was verified using nine common equine viruses. Clinical performance was evaluated by comparison with EIAV RT‐qPCR and AGID using samples derived from 196 inapparent EIAV carrier horses. Results: EIAV RT‐iiPCR did not react with other commonly encountered equine viruses and had equivalent sensitivity (95% detection limit of eight genome equivalents), with a concordance of 95.41% to conventional EIAV RT‐qPCR. However, the RT‐qPCR and RT‐iiPCR had sensitivities of 43.75 and 50.00%, respectively, when compared to the AGID test. Main limitations: Low viral loads commonly encountered in inapparent EIAV carriers may limit the diagnostic sensitivity of RT‐PCR‐based tests. Conclusions: Although EIAV RT‐iiPCR is not sufficiently sensitive to replace the current AGID test, it can augment control efforts by identifying recently exposed or "serologically silent" equids, particularly as the latter often represent a significant transmission risk because of high viral loads. Furthermore, the relatively low cost and field‐deployable design enable utilisation of EIAV RT‐iiPCR even in remote regions.